GAMBARAN HASIL PENYULUHAN TERHADAP PENGETAHUAN DAN SIKAP TENTANG KESIAPSIAGAAN BENCANA ERUPSI GUNUNG MARAPI PADA SISWA SMAN 1 SUNGAI PUA KABUPATEN AGAM 2020 - Budi Ikhwal Ramadhan, (2020)
The Republic of Indonesia is located geographically nor geologically, hidrologically, and demographically at the location where many volcanic related phenomenon and earthquakes frequently occur, its all because it stands on the pacific ring of fire, which is a volcanic circuit spreaded across the rim of the pacific ocean. Based on the collective data, from all the mountains that located on Indoesian soil, 60% of them are having huge potential to erupt. So, Preparedness is rather important to face the unforeseeable disaster, the lack of knowledge and awareness about the subject will certainly increase the rate of casualties. This research aims to analyze the High school students knowledge before and after the counselling about their preparedness for Mount Merapi eruption in SMA N 1 Sungai Pua, Agam Regency. The research instruments used were Questionnaire and Checklist Table. The sample collection technique was using random sampling by 74 respondents to adequate the population. The data is analyzed using univariate analysis. The results of descriptive analysis shows that their score on knowledge and attitude were increased. Their knowledge increased by 40,6% and their attitude increased by 35,2%. This shows that the counseling increased the students knowledge and attitude about preparedness for the mount merapi eruption. Hence, The students are expected to be able to implement this study on a daily basis and raise the other's awareness by sharing this study.